Artificial slope deformation monitoring and analyzing based on SBAS technology - Huang, Xiaochuan; Liu, Jincang; Yang, Ting; Li, Yun; Zhou, Lipeng (Frontiers in Earth Science, 2025)
Current research on geological disasters has predominantly focused on large-scale phenomena in specific regions, yet targeted safety evaluations and hazard identification for artificial slopes along mountainous highways remain underexplored, particularly through the application of Small Baseline Subset Interferometric Synthetic Aperture Radar (SBAS-InSAR). To address this gap, we employed the SBAS-InSAR methodology to analyze 44 Sentinel-1 SAR images spanning a highway slope region in Foshan City, Guangdong Province, integrating the slope’s construction timeline to temporally dissect deformation patterns and assess geological risks. Our results revealed a maximum annual average settlement rate of −35.69 mm/yr and a peak cumulative settlement of −28.9 mm, with deformation trends strongly correlated to construction phases—primarily concentrated between April 2022 and March 2023. Despite localized temporal disparities linked to varying construction schedules, the absence of large-scale anomalous settlement indicated robust geological conditions, while gradual stabilization suggested reduced long-term disaster risks. Spatially, settlement was concentrated at the slope base, accompanied by minor crest uplift. These findings underscore the critical role of SBAS-InSAR in monitoring infrastructure stability and mitigating environmental hazards. The study not only provides a practical framework for ensuring slope safety and sustainable highway operations but also advances methodologies for similar engineering projects, contributing to safer construction practices and informed disaster prevention strategies in geologically sensitive areas.